MYOCARDIAL INFARCTION AND EARLY PREVENTION METHODS (The Conference Hub, 2025)
Myocardial infarction (MI), or heart attack, remains one of the leading causes of death globally. It is primarily caused by a sudden reduction in coronary blood flow due to atherosclerotic plaque rupture and subsequent thrombosis. The condition leads to irreversible myocardial necrosis if not managed promptly. Major risk factors include hypertension, dyslipidemia, diabetes mellitus, smoking, obesity, sedentary lifestyle, and a family history of cardiovascular disease. Advances in preventive cardiology have highlighted the importance of early identification of at-risk individuals through regular screening, biomarker assessment, and non-invasive imaging techniques. Primary prevention focuses on lifestyle modifications, pharmacological management of risk factors, and public education, while secondary prevention targets individuals with established cardiovascular disease through strict control of contributing conditions and use of antiplatelet, statin, and antihypertensive therapies. This article aims to provide a comprehensive overview of myocardial infarction and the evidence-based strategies used for its early prevention, emphasizing the importance of a multidisciplinary and proactive approach in reducing incidence and improving outcomes.